Determinan Gizi Lebih dan Obesitas pada Remaja Usia 13-15 Tahun di DKI Jakarta (Analisis Data Riskesdas 2018): Determinan Gizi Lebih dan Obesitas pada Remaja Usia 13-15 Tahun di DKI Jakarta (Analisis Data Riskesdas 2018) - Ramadhany, Risya Amelia; Wahyuningsih, Utami; Sufyan, Dian Luthfiana; Simanungkalit, Sintha Fransiske (Universitas Airlangga, 2023)
Background: In 2018, the province of DKI Jakarta ranked first in obesity with a prevalence rate of 10% and second in overweight with a prevalence rate of 15.1% among adolescents aged 13-15 years. These figures exceed the national prevalence rate. Obesity has a negative impact on their quality of life. These effects include reduced mobility, academic performance, and various factors that can influence the occurrence of overweight and obesity in adolescents. Objectives:The objective of this study is to determine the determinants of overweight and obesity among adolescents aged 13-15 years in DKI Jakarta. Methods: This research design is a cross-sectional study that utilizes secondary data obtained from the 2018 Riskesdas (Indonesia basic health research) survey, with a sample size of 597 adolescent respondents aged 13-15 years. Bivariate analysis was conducted using chi-square, and multivariate analysis was performed using logistic regression. Results:The results of the bivariate analysis show that maternal education (p=0.001) and energy drinks (p=0.036) have an influence on the occurrence of obesity in adolescents. In the multivariate analysis, it is revealed that the variable that most significantly and statistically affects the occurrence of obesity in adolescents is mother's education, with an odds ratio (OR) value of 1.895 and a CIf1.305-2.752. Conclusions: The determinants of overweight and obesity among adolescents aged 13-15 years in DKI Jakarta are mother's education, with an ap value of 0.001 and an odds ratio (OR) value of 1.895. This means that mothers with lower education levels have a 1.895 times higher risk of having adolescents with obesity status.